Evaluation of roughness and micromorphology of epoxy paint on cobalt-chromium alloy before and after thermal cycling - Alessandra Cardoso da Silva Nascimento; Carlos Alberto Muzilli; Milton Edson Miranda; Flávia Martão Flório; Roberta Tarkany Basting (Sociedade Brasileira de Pesquisa Odontológica, 2013)
It has been suggested that the epoxy paint used to coat metal substrates in industrial electrostatic painting applications could also be used to mask metal clasps in removable dental prostheses (RDP). The purpose of this study was to evaluate both the influence of thermal cycling and the in vitro roughness of a surface after application of epoxy paint, as well as to assess the micromorphology of a cobalt-chromium (CoCr) based metal structure. Sixty test specimens were fabricated from a CoCr alloy. The specimens were separated into three groups (n = 20) according to surface treatment: Group 1 (Pol) - polished with abrasive stone and rubbers; Group 2 (Pol+Epo) - polished and coated with epoxy paint; Group 3 (Epo) - air-abraded with aluminum oxide particles and coated with epoxy paint. The surface roughness was evaluated before and after 1000 thermal cycles (5°C and 50°C). The surface micromorphology was verified by scanning electron microscopy (SEM). The two-way repeated measures ANOVA showed significant differences among surface treatments (p < 0.0001), but no difference was found before and after thermal cycling (p = 0.6638). The CoCr-based metal alloy surfaces treated with epoxy paint (Groups 2 and 3) were rougher than the surfaces that were only polished (Group 1). Thermal cycling did not influence surface roughness, or lead to chipping or detachment of the epoxy paint.